Hubungan Kecemasan Dengan Tension-Type Headache Di Poliklinik Saraf RSUD Dr. Moewardi Surakarta - , Fardhika, dr. Listyo Asist Pujarini, M.Sc, Sp.S, dr. Dona Dewi Niriawati (2015)
Background: In developing country include Indonesia, the prevalence of TTH is still high. Tension-type Headache (TTH) is front and back of head pain condition. The contraction of head and neck muscle causing the pain which stimulated by psychogenic factors such as stress, anxiety, depression, local disease on head and neck. But some research get results that factors anxiety is not related to TTH. Objective: To evaluate the association between anxiety and tension-type headache in Neurologic Clinic of Dr. Moewardi General Hospital Surakarta. Metode: Observational analytic using cross sectional methods. 44 samples are taken based on purposive sampling technique. Data in tables is analyzed using Chi Square. Result: Test with p = 0,003 measured using Depression Anxiety Stress Scale (DASS) which has been validated. Odds Ratio (OR) 7,111 (95%CI;[1,887-26,804]) with Ratio Prevalency (RP) = 2,66 or > 1 which means notion of risk factor to the disease is true. Conclusion: There is association between anxiety and tension-type headache